3D eddy currents computation by BEM using the modified magnetic vector potential and the reduced magnetic scalar potential. (11th July 2019) - Phan, Quang‐Anh; Meunier, Gerard; Chadebec, Olivier; Guichon, Jean‐Michel; Bannwarth, Bertrand
Abstract: A new boundary element method (BEM) formulation has been developed for the computation of 3D eddy currents in both magnetic and conductive regions. The modified magnetic vector potential A ∗ in the active regions and the reduced magnetic scalar potential φ in the air are used as unknown variables. The formulation is limited to low‐frequency magneto‐harmonic problems associated to linear, homogeneous, isotropic, and simply‐connected regions. In such a configuration, it leads to accurate results with a reduced number of degrees of freedom located on a surface mesh delimiting the air/material interface.